Mechanisms and Approaches for Overcoming Enzalutamide Resistance in Prostate Cancer - Vander Ark, Alexandra; Cao, Jingchen; Li, Xiaohong (Frontiers in Oncology, 2018)
Enzalutamide, a second-generation small-molecule inhibitor of the androgen receptor, has been approved for patients who failed with androgen deprivation therapy and have developed castration-resistant prostate cancer. More than 80% of these patients develop bone metastases. The binding of enzalutamide to the androgen receptor prevents the nuclear translocation of the receptor, thus inactivating androgen signaling. However, prostate cancer cells eventually develop resistance to enzalutamide treatment. Studies have found resistance both in patients and in laboratory models. The mechanisms of and approaches to overcoming such resistance are significant issues that need to be addressed. In this current review, we focus on the major mechanisms of acquired enzalutamide resistance, including genetic mutations and splice variants of the androgen receptor, signaling pathways that bypass androgen signaling, intratumoral androgen biosynthesis by prostate tumor cells, lineage plasticity, and contributions from the tumor microenvironment. Approaches for overcoming these mechanisms to enzalutamide resistance along with the associated problems and solutions are discussed. Emerging questions, concerns, and new opportunities in studying enzalutamide resistance will be addressed as well.